Do eco-rating schemes improve the environmental performance of ships?. (January 2018) - Poulsen, René Taudal; Hermann, Roberto Rivas; Smink, Carla K.
Abstract: This paper examines if eco-rating schemes improve environmental outcomes in the context of the international shipping industry. Shipping faces global environmental challenges and has recently witnessed the introduction of several eco-rating schemes aiming to improve the environmental performance of ships. Extending the private environmental governance literature into a mature service industry with global operations, the paper shows that concerns about eco-rating schemes' effectiveness also have relevance here. Shipping eco-rating schemes fall short of best practices for design and governance, and this hampers improvement efforts. The study has policy implications for the achievement of improved environmental outcomes in the shipping industry. Highlights: Environmental effectiveness of shipping industry eco-rating schemes is studied. In terms of design and governance eco-rating schemes fall short of best practices. Stakeholder aims differ and this reduces eco-rating schemes' effectiveness. The full potential for improved environmental outcomes is not achieved. Concerns on eco-rating schemes' effectiveness are relevant in service industries.